"Dahon" exploring the visual metaphor of ephemerality and continuity of time through an installation of dried cured seagrape leaves - Escario, Maria Cristina S.; Vinluan, Nestor Olarte; Austria, Romanlito Salvador (Quezon City College of Fine Arts, University of the Philippines Diliman, 2023)
Time is the central theme of this thesis. The process and seasons of time are represented in the materials used and how it is formed. I used dry leaves as the main material for my installation, as well as the language of my narrative. "Dahon" is a visual narrative that embraces the method of autoethnography. I used the metaphor of dry leaves, dahon's design, and its formation process to describe my observation of the natural environment; and reflect the connections I have seen, which allow me to understand life's season and the meaning of time. The work is presented through approximation of the golden mean or Fibonacci sequence in its structural design and the configuration of the work's unit, which is the leaf. The use of this pattern aims to convey the ebb and flow, and continuity of life, both of human and of nature. I have chosen dried leaves because of their ordinariness. Dry leaves are common in our environment, rarely noticed or appreciated, yet if studied closely they manifest the observable fact of the life cycle of all living things. It reflects life's simplicity and complexity.

This thesis is a study of process. The completion of the artwork involved strict adherence to time and a long process of waiting. The season is observed in the collection of the primary material. Also, time is measured in the observance of the transition of the physiological characteristics of leaves. The use of organic materials in the work has arisen as a reaction against the use of synthetic and harsh chemical-based products in my previous works. Glycerin is applied to delay decomposition. Yet, nature takes over the process, and eventually, the need to heed to it arises. This occurrence adhering to nature's process expresses the futility that we humans do to control time.

Change, cyclical process, seasons, transience, and infinity are words that embody time in my art installation. Aged materials represent the passage of time. Combining these concepts with the self-similarity theory of Fibonacci--the blueprint of creation--Dahon aims to evoke a visceral experience from the audience; tapping unconscious to deepen people's understanding and appreciation of the transitoriness and the passing of life and time, as elements of a beautiful, well-planned design by God.
Thesis (Master of Fine Arts)--University of the Philippines Diliman
Bibliography: leaves 140-142
Keywords: Art installation; Ephemeral; Leaves in art; Nature (Aesthetics)